ANALYZING THE IMPACT OF GREEN TRAINING ON COMPETENCIES DEVELOPMENT USING PLS-SEM -CASE STUDY: CHIALI COMPANY - Abdelkader el Amir , RAFFAR (The journal of contemporary issues in business and government, 2024)
This study aims to show the impact of green training on competencies development in Chiali company. We took a sample of 85 individuals who are distributed on different professional categories. After treating data of a sample of 79 individuals using SmartPLS3, the results show the following: There is a positive impact of training needs assessment on competencies development for Chiali company. Moreover, there is a positive impact of training design on competencies development for Chiali company, there is a positive impact of training effectiveness on competencies development for Chiali company, finally, there is a positive impact of training evaluation on competencies development for Chiali company.